Small G Proteins Dexras1 and RHES and Their Role in Pathophysiological Processes. (20th March 2014) - Thapliyal, Ashish; Verma, Rashmi; Kumar, Navin
Abstract : Dexras1 and RHES, monomeric G proteins, are members of small GTPase family that are involved in modulation of pathophysiological processes. Dexras1 and RHES levels are modulated by hormones and Dexras1 expression undergoes circadian fluctuations. Both these GTPases are capable of modulating calcium ion channels which in turn can potentially modulate neurosecretion/hormonal release. These two GTPases have been reported to prevent the aberrant cell growth and induce apoptosis in cell lines. Present review focuses on role of these two monomeric GTPases and summarizes their role in pathophysiological processes.